Turning A => M[B] into M[A => B]

In Practice

No, it can not be done, at least not in a meaningful way.

Consider this Haskell code

action :: Int -> IO String
action n = print n >> getLine

This takes n first, prints it (IO performed here), then reads a line from the user.

Assume we had an hypothetical transform :: (a -> IO b) -> IO (a -> b). Then as a mental experiment, consider:

action' :: IO (Int -> String)
action' = transform action

The above has to do all the IO in advance, before knowing n, and then return a pure function. This can not be equivalent to the code above.

To stress the point, consider this nonsense code below:

test :: IO ()
test = do f <- action'
          putStr "enter n"
          n <- readLn
          putStrLn (f n)

Magically, action' should know in advance what the user is going to type next! A session would look as

42     (printed by action')
hello  (typed by the user when getLine runs)
enter n
42     (typed by the user when readLn runs)
hello  (printed by test)

This requires a time machine, so it can not be done.

In Theory

No, it can not be done. The argument is similar to the one I gave to a similar question.

Assume by contradiction transform :: forall m a b. Monad m => (a -> m b) -> m (a -> b) exists.
Specialize m to the continuation monad ((_ -> r) -> r) (I omit the newtype wrapper).

transform :: forall a b r. (a -> (b -> r) -> r) -> ((a -> b) -> r) -> r

Specialize r=a:

transform :: forall a b. (a -> (b -> a) -> a) -> ((a -> b) -> a) -> a

Apply:

transform const :: forall a b. ((a -> b) -> a) -> a

By the Curry-Howard isomorphism, the following is an intuitionistic tautology

((A -> B) -> A) -> A

but this is Peirce’s Law, which is not provable in intuitionistic logic. Contradiction.

Leave a Comment